Pengaruh Likuiditas Dan Solvabilitas Terhadap Profitabilitas Pada PT Prima Cakrawala Abadi Tbk Dan PT Pratama Abadi Nusa Industri Tbk Periode 2022–2024 - Aulya, Rabiatul; Puji Muniarty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the effect of liquidity and solvency on profitability at PT Prima Cakrawala Abadi Tbk and PT Pratama Abadi Nusa Industri Tbk during the 2022–2024 period. The research applies a quantitative approach using secondary data from financial statements. Data analysis is conducted through financial ratios and multiple linear regression.The results indicate that liquidity has a positive effect on profitability, while solvency has a negative effect. Simultaneously, both variables significantly influence profitability, highlighting the importance of effective financial management.